Wafer-scale monolayer MoS2 grown by chemical vapor deposition using a reaction of MoO3 and H2S. (7th April 2016) - Kim, Youngchan; Bark, Hunyoung; Ryu, Gyeong Hee; Lee, Zonghoon; Lee, Changgu
Abstract: Monolayer MoS2 nanosheets are potentially useful in optoelectronics, photoelectronics, and nanoelectronics due to their flexibility, mechanical strength, and direct band gap of 1.89 eV. Experimentalists have studied the synthesis of MoS2 using chemical vapor deposition (CVD) methods in an effort to fabricate wafer-scale nanofilms with a high uniformity and continuity for practical electronic applications. In this work, we applied the CVD method to a reaction of MoO3 powder and H2 S gas to grow high-quality polycrystalline monolayer MoS2 sheets with unprecedented uniformity over an area of several centimeters. The monolayer MoS2 was characterized using Raman spectroscopy, photoluminescence (PL) spectroscopy, atomic force microscopy (AFM), x-ray photoemission spectroscopy (XPS), and transmission electron microscopy (TEM). The top-gate field-effect transistor prepared with a 30 nm HfO2 capping layer displayed an electrical mobility of 1 cm 2 v −1 s −1 and an I on/off of ~10 5 . This method paves the way for the development of practical devices with MoS2 monolayers and advances fundamental research.